Pengaruh Perbedaan Gender pada Hubungan Independensi Auditor terhadap Kualitas Audit - Utama, Fikri Rizki; Juniyanto, Endri; Fatriansyah, Alif Ilham Akbar (Budgeting: Jurnal Akuntansi Syariah, 2024)
This research aims to empirically examine the influence of auditor independence on audit quality and how gender differences moderate this relationship. The study employs a survey method. The sampling criteria were public accountants who worked at the Public Accounting Firm (KAP) in Bandar Lampung City. Primary data were collected through questionnaires and analyzed using the Smart PLS program. The findings indicate that auditor independence does not significantly affect audit quality. Additionally, gender differences do not moderate the relationship between auditor independence and audit quality.